Looking glass sound - Ward, Catriona (Nightfire/Tor Publishing Group, 2023)
"In a lonely cottage overlooking the windswept Maine coast, Wilder Harlow begins the last book he will ever write. It is the story of a sun-drenched summer of his youth, and of the killer that stalked the small New England town. And of the terrible tragedy that forever bonded him with his friends Nat and Harper in unknowable ways. Decades later, Wilder returns to the town in an attempt to recount that summer's events in his memoirs. But as he writes, Wilder begins to fear his grip on the truth is fading ... and that the book may be writing itself."--